2020
DOI: 10.3390/jcm9041121
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Lifestyle Patterns are Associated with Heart Rate Variability

Abstract: Assessment of heart rate variability (HRV) and cardiac ectopic beats is a clinically relevant topic. The present exploratory observational study aimed to inspect the relationships of lifestyle, dietary patterns, and anthropometrics with HRV, premature ventricular complexes (PVCs), and supraventricular premature complexes (SVPCs). A cross-sectional study enrolling subjects undergoing Holter monitoring was performed. Sociodemographic and clinical characteristics, body composition (full-body bio-impedentiometry),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Associations of a single dietary component (e.g., fat or sodium intake, nut consumption) with HRV have been reported in several studies; as reviewed by Young and Benton [ 27 ], the current evidence points towards an association between healthy aspects of diet and higher HRV. In line with this, a recent observational study by Reginato et al [ 28 ] reported a positive association between fruit consumption and HRV. Considering diet more broadly, the Mediterranean diet has been shown to associate with higher HRV [ 29 ].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Associations of a single dietary component (e.g., fat or sodium intake, nut consumption) with HRV have been reported in several studies; as reviewed by Young and Benton [ 27 ], the current evidence points towards an association between healthy aspects of diet and higher HRV. In line with this, a recent observational study by Reginato et al [ 28 ] reported a positive association between fruit consumption and HRV. Considering diet more broadly, the Mediterranean diet has been shown to associate with higher HRV [ 29 ].…”
Section: Introductionsupporting
confidence: 74%
“…Better sleep-time recovery, measured by the ratio between stress and recovery during sleep (Stress Balance), was significantly associated with higher fibre intake and higher overall diet quality, supporting previous–although scarce–literature. Higher HRV measured in a laboratory setting has been associated with health-promoting features of diet, such as higher intake of green leafy vegetables [ 33 ] and fruit [ 28 ], adherence to the Mediterranean diet [ 29 ], and higher diet quality [ 21 ]. In our study, weaker recovery, measured by both RMSSD and Stress Balance, was also associated with higher reported long-term alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study compares HRV parameters across a range of BMIs in an early childhood population. Whilst BMI can be a reliable indicator of weight status in normal weighted populations, it is not a measure of body fat and does not account for sex and age, which are important factors to consider for early childhood growth patterns ( Kwieciński et al, 2018 , Reginato et al, 2020 ). Also, confounding factors such as environment (indoor vs outdoor measurements), sleep, diet, physical activity over the entire day or outside of the early learning centre, cardiorespiratory fitness, socioeconomic status, race/ethnicity and behaviour were not controlled for [50].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature about the central role of dietary components in the prevention of cardiac arrhythmias, especially fatal arrhythmias (ventricular arrhythmias), but little evidence is available regarding the protective effects of dietary patterns and lifestyle on premature ventricular complexes (PVCs) and HRV [ 62 , 63 ].…”
Section: Effects Of Diet On Heart Rate Variabilitymentioning
confidence: 99%
“…This study also showed a significant direct association between waist circumference and PVCs and an inverse correlation between fruit intake and PVCs. Higher consumption of sweets, sugars, and refined grain products led to an increase of the number of PVCs [ 63 ]. From previous investigations, limited evidence is available regarding the association between protein food and cardiac electrical activity, since earlier studies have concentrated mainly on fish intake and cardiac rhythm, not on another type of protein food.…”
Section: Effects Of Diet On Heart Rate Variabilitymentioning
confidence: 99%